EMG and heart rate responses decline within 5 days of daily whole-body vibration training with squatting. - André Rosenberger (Public Library of Science (PLoS), 2014)
In this study, we examined the acute effects of a 5-day daily whole-body vibration (WBV) training on electromyography (EMG) responses of the m. rectus femoris and m. gastrocnemius lateralis, heart rate (HR, continuously recorded), and blood lactate levels. The purpose of the study was to investigate the adaptation of muscle activity, heart rate and blood lactate levels during 5 days of daily training. Two groups of healthy male subjects performed either squat exercises with vibration at 20 Hz on a side alternating platform (SE+V, n = 20, age  = 31.9±7.5 yrs., height  = 178.8±6.2 cm, body mass  = 79.2±11.4 kg) or squat exercises alone (SE, n = 21, age  = 28.4±7.3 years, height  = 178.9±7.4 cm, body mass  = 77.2±9.7 kg). On training day 1, EMG amplitudes of the m. rectus femoris were significantly higher (P<0.05) during SE+V than during SE. However, this difference was no longer statistically significant on training days 3 and 5. The heart rate (HR) response was significantly higher (P<0.05) during SE+V than during SE on all training days, but showed a constant decline throughout the training days. On training day 1, blood lactate increased significantly more after SE+V than after SE (P<0.05). On the following training days, this difference became much smaller but remained significantly different. The specific physiological responses to WBV were largest on the initial training day and most of them declined during subsequent training days, showing a rapid neuromuscular and cardiovascular adaptation to the vibration stimulus.